Mosquito oviposition and larvae development in response to kairomones originated by different fish. Issue 1 (18th June 2020) - Cohen, S.; Silberbush, A.
Abstract: Predator‐released kairomones indicating the presence of predatory fish are known to alter the behaviour and life‐history traits of several aquatic herbivores. Culex mosquitoes (Diptera: Culicidae) respond to such cues by altering oviposition habitat selection and larval development time. These responses differ among fish species indicating composition differences among fish‐released cues, but the recognition pattern is not clear. This study tested the dependence of fish recognition to co‐evolution and the level of threat to larvae. We compared Culex responses to three fish, the invasive larvivorous Gambusia affinis (Cyprinodontiformes: Poeciliidae), the native larvivorous Aphanius mento (Cyprinodontiformes: Cyprinodontidae) and the native algivorous Garra rufa (Cypriniformes: Cyprinidae). The effects of cues released by the three fish on Culex oviposition and life‐history shifts were compared in field mesocosms and lab tests. Our results showed that ovipositing females were significantly repelled only by cues originated from G. affinis, while developing larvae response was a more general one. Our results support the idea that fish‐released kairomones differ in composition or quantities among different species. Abstract : Mosquitoes from the Genus Culex respond to kairomones indicating the presence of larvivorous fish in several ways. Ovipositing Culex female are strongly repelled from kairomones released by invasive Gambusia affinis fish. Response to two native fish was much weaker. Culex larvae metamorphose faster when exposed to kairomone cues from all three fish.